The multi-faced role of FUNDC1 in mitochondrial events and human diseases - Tan, Nannan; Liu, Tianhua; Wang, Xiaoping; Shao, Mingyan; Zhang, Miao; Li, Weili; Ling, Guanjing; Jiang, Jinchi; Wang, Qiyan; Li, Jing; Li, Chun; Wang, Wei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Mitophagy plays a vital role in the selective elimination of dysfunctional and unwanted mitochondria. As a receptor of mitophagy, FUN14 domain containing 1(FUNDC1) is attracting considerably critical attention. FUNDC1 involves in the mitochondria fission, the clearance of unfolded protein, iron metabolism in mitochondria, and the crosstalk between mitochondria and endoplasmic reticulum besides mitophagy. Studies have demonstrated that FUNDC1 is associated with the progression of ischemic disease, cancer, and metabolic disease. In this review, we systematically examine the recent advancements in FUDNC1 and the implications of this protein in health and disease.